Programmable logic controllers - Petruzella, Frank D. (McGraw-Hill Higher Education, 2005)
Now in four-color, this outstanding text for the first course in programmable logic controllers (PLCs) focuses on how PLCs work and gives students practical information about installing, programming, and maintaining PLC systems. It's not intended to replace manufacturer's or user's manuals, but rather complements and expands on the information contained in these materials. All topics are covered in small segments. Students systematically carry out a wide range of generic programming exercises and assignments. All of the information about PLCs has been updated.